Governance Structures: A Complementary Study Of Transaction Costs, Measurement Costs And Strategic Resources - Augusto, Cleiciele Albuquerque; Souza, José Paulo de (Revista Gestão da Produção Operações e Sistemas, 2017)
The objective of this study is to understand how governance structures are formed, considering transaction costs, measurement costs and strategic resources. To that end, bibliographic research was carried out in order to explore the complementarity of three theories: Transaction Cost Theory (TCT),Measurement Cost Theory (MCT) and Resource-Based View (RBV). A combined approach indicates that having strategic resources (RBV) may characterize a property right that needs to be protected by governance structures that consider transaction attributes and behavioral assumptions (TCT) andthe measurability of resources involved (MCT) in transactions.